Impact of COVID-19 on inpatient care related to skin conditions - Kalanj, Karolina; Orbanić, Ante; Peček, Mirta; Orešković, Stjepan; Marshall, Rick; Šitum, Mirna (Frontiers in Medicine, 2023)
Background: The COVID-19 pandemic significantly affected our society and healthcare system. This study aims to evaluate the effects of COVID-19 on the number of hospitalized patients with dermatological diseases in Croatia, as well as the number of these patients treated surgically and conservatively before and during the pandemic. Materials and Methods: This is a retrospective, comparative study of the hospital admission rate for the MDC-09 group, a collection of Skin, Subcutaneous Tissue, and Breast disorders before and during the pandemic. This study used data from the Croatian Institute of Public Health (CIPH) and the Croatian Health Insurance Fund (CHIF). Inpatient data for the CHIF data collection were categorized using the Australian Refined Diagnosis Related Groups (AR-DRGs). All hospital admissions for dermatology patients in the MDC-09 group at all non-specialized hospitals in Croatia were tracked during two periods, before (2017-2019) and during the pandemic (2020-2021). Results: The average number of dermatology patients in all hospitals fell by 29% during the pandemic. The overall number of dermatological patients admitted to hospitals fell by 32% in 2020 and 26% in 2021 compared to the average number of patients admitted each year over the preceding three years. Additionally, there was an average 22% fall in surgical procedures during the pandemic. The only exception for surgical procedures is Major Breast Reconstruction, which is noted an increase, as also for Malignant Breast Disorders, Minor Complexity, and Major Skin Disorders, Minor Complexity in a group of non-surgically treated patients. Conclusion: Examining all the consequences of the Croatian dermatological patient care interruption will require more investigation. Reduced access to medical care during the pandemic is anticipated to lead to later illness diagnosis, a later start to treatment, a poorer disease prognosis, and higher medical expenditures.